2020
DOI: 10.3390/jcm9072148
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertensive Intracerebral Hemorrhage with Left Ventricular Hypertrophy on Transthoracic Echocardiography

Abstract: Introduction: Arterial hypertension is the most frequent cause for spontaneous intracerebral hemorrhage (sICH) and may also cause left ventricular hypertrophy (LVH). We sought to analyze whether hypertensive sICH etiology is associated with LVH. Methods: We analyzed consecutive patients with sICH who were admitted to our tertiary stroke center during a four-year period and underwent transthoracic echocardiography (TTE) as part of the diagnostic work-up. We defined hypertensive sICH as typical localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Although some studies have reported increased frequency of hypertension in patients with HTN-cSVD compared with those with CAA,2 several other studies have demonstrated similar burdens of vascular risk factors between these two cSVD groups 8 28 29. Our study also did not show any differences between the frequency of vascular risk factors between the four cSVD groups among patients with isolated-LICH.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Although some studies have reported increased frequency of hypertension in patients with HTN-cSVD compared with those with CAA,2 several other studies have demonstrated similar burdens of vascular risk factors between these two cSVD groups 8 28 29. Our study also did not show any differences between the frequency of vascular risk factors between the four cSVD groups among patients with isolated-LICH.…”
Section: Discussioncontrasting
confidence: 67%
“…A single lobar ICH probably represents a relatively early phase of cerebral injury even among HTN-cSVD and this might explain the lack of significant differences in risk factor load. As reported in other studies, the admission blood pressure was not significantly different between patients with HTN-cSVD pattern and CAA pattern suggesting that the binary variable of hypertension (ie, the presence or absence) is a relatively non-specific risk factor that is unreliable at predicting underlying cSVD aetiology 8. To increase our ability to discriminate cSVD aetiologies, we employed LVH as sensitive non-invasive cardiac biomarker that has been associated with the presence of HTN-cSVD 8 28 30.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Lens contamination caused by the active bleeding can cause the doctor’s vision to be blurred. Hemostasis is relatively difficult, suggesting that preoperative evaluation should be done, and craniotomy planning should be performed, if necessary[ 15 ].…”
Section: Discussionmentioning
confidence: 99%